Ability of alpha-lipoic acid to reverse the diabetic cystopathy in a rat model - Jiang Yuan-jun; Gong Da-xin; Liu Hai-bo; Yang Chun-ming; Sun Zhi-xi; Kong Chui-ze (Acta Pharmacologica Sinica, 2016)
Aim: The present study was conducted to investigate whether alpha-lipoic acid (α-LA) is able to reverse impaired bladder function induced by diabetes in a rat model and to explore the possible mechanism mediating the effect. Methods: Male Sprague-Dawley rats were divided randomly into 3 age-matched groups: control, diabetes mellitus (DM) treated with vehicle, and DM with α-LA treatment. The diabetic rats were induced by a single intraperitoneal (ip) injection of streptozotocin (60 mg/kg). Six weeks after the induction of DM, the two groups received another 6 weeks of treatment with vehicle or α-LA (100 mg/kg, ip). Body weight and blood glucose levels were measured weekly. The bladder function was evaluated by in vitro cystometry. The oxidative stress status was determined by biochemical methods, and the level of nerve growth factor was investigated by enzyme-linked immunosorbent assay. Results: The streptozotocin-induced diabetic rats showed impaired bladder function characterized by increased bladder capacity, decreased bladder contractility (voiding efficiency), and an increase in residual urine. Treatment with α-LA significantly normalized the increased bladder capacity for inducing voiding, single-voided volume, and post-void residual volume. α-LA treatment significantly reversed the increased level of malondialdehyde and reduced the activities of both superoxide dismutase and catalase. DM caused a decrease in the bladder nerve growth factor (NGF) level, and α-LA upregulated the level of NGF in the diabetic rat bladder. Conclusion: These results indicate that α-LA has a beneficial effect on diabetes-induced cystopathy by ameliorating oxidative stress and normalizing the NGF level in the bladder.